BALB/c Mice Can Learn Touchscreen Visual Discrimination and Reversal Tasks Faster than C57BL/6 Mice - Turner, Karly M.; Simpson, Christopher G.; Burne, Thomas H. J. (Frontiers in Behavioral Neuroscience, 2017)
Touchscreen technology is increasingly being used to characterise cognitive performance in rodent models of neuropsychiatric disorders. Researchers are attracted to the automated system and translational potential for touchscreen-based tasks. However, training time is extensive and some mouse strains have struggled to learn touchscreen tasks. Here we compared the performance of commonly used C57BL/6J mice against the BALB/c mice, which are considered a poor performing strain, using a touchscreen task. BALB/c and C57BL/6J mice were trained to operate the touchscreens before learning a visual discrimination and reversal task. Following touchscreen testing, these strains were assessed for differences in locomotion and learned helplessness. BALB/c mice finished training in nearly half the number of sessions taken by C57BL/6J mice. Following training, mice learned a visual discrimination task where BALB/c mice again reached criteria in fewer than half the sessions required for C57BL/6J mice. Once acquired, there were no strain differences in % correct responses, correction trials or response latency. BALB/c mice also learnt the reversal task in significantly fewer sessions than C57BL/6J mice. On the open field test C57BL/6J mice travelled further and spent less time immobile than BALB/c mice on the forced swim test. After touchscreen testing, strains exhibited well-established behavioural traits demonstrating the extensive training and handling from touchscreen testing did not alter their behavioural phenotype. These results suggest that BALB/c mice can be examined using touchscreen tasks and that task adaptations may improve feasibility for researchers using different strains.